2007
DOI: 10.1515/ijamh.2007.19.1.99
|View full text |Cite
|
Sign up to set email alerts
|

Psychological autopsy studies: The role of alcohol use in adolescent and young adult suicides

Abstract: Alcohol abusers seem to be prone to both suicide attempts and completions. The relationship between alcohol abuse and suicide in adolescence is complex. Objectives: To examine the role of alcohol abuse and dependence in adolescent suicide in psychological autopsy studies. Method: A search in the National Library of Medicine (NLM) PubMed database using "adolescents" and "all child: 0-18 years" as the search terms for age and "psychological autopsy" as the search term for title or abstract. Results: Forty articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 7 publications
0
6
0
1
Order By: Relevance
“…Also substance misuse not fulfilling the diagnostic criteria of substance use disorders has been reportedly associated with adolescent suicides [18]. In a recent review Giner et al [56] found that the role of alcohol use in adolescent and young adult suicides was high (from 21.4% to 43.7%). Schizophrenic psychoses and personality disorders have been diagnosed more commonly in young adult than adolescent suicides, while disruptive disorders and adjustment disorders have been more prevalent among younger victims.…”
Section: Findings In Psychological Autopsy Studiesmentioning
confidence: 99%
“…Also substance misuse not fulfilling the diagnostic criteria of substance use disorders has been reportedly associated with adolescent suicides [18]. In a recent review Giner et al [56] found that the role of alcohol use in adolescent and young adult suicides was high (from 21.4% to 43.7%). Schizophrenic psychoses and personality disorders have been diagnosed more commonly in young adult than adolescent suicides, while disruptive disorders and adjustment disorders have been more prevalent among younger victims.…”
Section: Findings In Psychological Autopsy Studiesmentioning
confidence: 99%
“…Regarding personal factors in predicting adolescent suicide, various studies suggest that depression (Brent et al, 1994; Connell & Meyer, 1991; Kessler & Walters, 1998), self‐esteem (Wilburn & Smith, 2005), gender (Goldacre & Hawton, 1985), academic performance (Martin, Richardson, Bergen, Roeger, & Allison, 2005), and dropping out of school (Thompson & Eggert, 1999) are associated with suicidal behaviors. Different studies have also verified the correlation between adolescent suicides and variations regarding adolescent abuse of alcohol and drugs (Giner et al, 2007). Meanwhile, parents' alcohol and drug abuse also have an important relationship with adolescent suicidal behaviors (Pfeffer, Normandin, & Kakuma, 1998).…”
mentioning
confidence: 98%
“…Alcohol consumption is one of the most significant proximal risk factors for suicidal behaviour 2 . When alcohol is consumed in the minutes or hours before the attempt, henceforth described as ‘acute alcohol consumption’, suicide attempts are more likely to become suicides 3 . An international review reported anywhere between 10% and 69% of suicide cases contain a positive blood alcohol concentration (BAC) at time of death 4 …”
mentioning
confidence: 99%
“…We hypothesise that areas with higher proportions of alcohol‐related suicide will be areas previously shown to have higher rates of suicides. Currently, there is little research investigating the spatial variation in the number of alcohol‐related suicides in Australia, however, research has previously demonstrated variations in consumption of alcohol 10 and suicide, 7,8 and that alcohol is a risk factor for suicide 11 . The study uses geospatial data analysis and visualisation techniques on suicide data (between 2010 and 2015) obtained from the National Coronial Information System (NCIS).…”
mentioning
confidence: 99%